Urban impacts on river functionality: semi-arid rivers of America and Europe - Vega-Aguilar, Aylet; Ojeda, Alfredo Ollero; Yépez-Rincón, Fabiola Doracely; González, Kevin David Rodríguez; Limón, Daniel Salas (Geografares, 2026)
Urban rivers exhibit profound alterations in their hydrological and geomorphological dynamics as a consequence of urban sprawl, floodplain development, and infrastructure construction. This study evaluates the hydrogeomorphological quality of two urban rivers in semi-arid regions of the Americas (Mexico) and Europe (Spain) using the Hydrogeomorphological Index. The methodology integrates spatial analysis, fieldwork, historical hydrological data, and the delineation of functional reaches. The results reveal a marked contrast between urban and peri-urban reaches, with the former showing the lowest hydrogeomorphological quality values, associated with channel fragmentation, altered flow regimes, and degradation of the riparian corridor. Based on the diagnosis, the implications for the management and improvement of urban rivers are discussed, through a set of measures aimed at functional restoration and enhancing socio-environmental resilience.
Keywords: urban rivers; fluvial geomorphology; semi-arid basins